Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

how to solve dy/dt+2y=exp(t/2)

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

Use an inegrating factor: This equation is in the format: \[dy/dt + 2y = e^{t/2}\] \[dy/dt + P(x)y = Q(x)\]
Use an inegrating factor: This equation is in the format: dy/dt + 2y = e^{t/2} dy/dt + P(t)y = Q(t) I.f. = e^(int[P(t)dt])
I.f. = e^[Integral(2dt)] = e^(2t) Multiply your diff equation by the integrating factor e^(2t) e^(2t) * [dy/dt+2y] = e^(2t) * e^(t/2)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

I.f. = e^[Integral(2dt)] = e^(2t) Multiply your diff equation by the integrating factor e^(2t); e^(2t) * [dy/dt+2y] = e^(2t) * e^(t/2)
Sorry for double post my pc is having issues. Now simplify: (dy/dt)*e^(2t) + 2y*e^(2t) = e^(2t + [t/2]); Notice the left side is a product rule for derivatives: (d/dt)[y*e^2t] = e^(5t/2); {Btw if you don't understand how i got the left side; differentiate that product with respect to t, you just have to recognize the form and the reason why we use integrating factors is because we want to put one side of the d.e. into that form: y*2*e^(2t) + e^(2t)*(dy/dt)}
So now you know that: (d/dt)[y*e^(2t)]=e^(5t/2) {derivative of y*e^(2t) with respect to t is equal to e^(5t/2)} Integrate both sides with respect to t: (d/dt)[y*e^(2t)]=e^(5t/2) Int{ (d/dt)[y*e^(2t)] * dt}=Int{ e^(5t/2) * dt }
Integral of the derivative is just the original function (i think it is called newton's method or something like that). So the integral of the left side is: y*e^(2t) = Integral(e^[5t/2]*dt); the right side is easy to integrate: Integral(e^[5t/2]*dt); Let u = 5t/2; then du = (5/2) dt; Multiply the integral by (2/5)*(5/2) - Basically im multiplying by one, i just need that 5/2 for the du; so: Integral(e^[5t/2]*dt) = (2/5)* Integral(e^u * du) = (2/5)*e^u +C
We let u = 5t/2, so: y*e^(2t) = (2/5)*e^u +C y*e^(2t) = (2/5)*e^(5t/2) +C
Simplify (divide everything by e^(2t)): y*e^(2t) = (2/5)*e^(5t/2) + C y = (2/5) * e^([5t/2] - [2t]) + C * e^(-2t) y = (2/5) * e^(t/2) + C*e^(-2t) <= Your answer
Simplify (divide everything by e^(2t)): y*e^(2t) = (2/5)*e^(5t/2) + C; y = (2/5) * e^([5t/2] - [2t]) + C * e^(-2t); y = (2/5) * e^(t/2) + C*e^(-2t) <= Your answer
Sorry for double post again, im havin issues with pc.. So that's the method u use to solve these types of problems. My answer should be correct, just check my arithmetic, i had a class early in the morning and have a break now solved this without a calculator, but i think there shouldn't be any mistakes, but just in case check the work. But that's how u solve those problems. Btw, my next class is differential equations!

Not the answer you are looking for?

Search for more explanations.

Ask your own question